Technological Prospection of Pequizeiro (Caryocar brasiliense Camb.) (Research, Society and Development, 2020)
The Caryocar brasiliense Camb. (pequizeiro) is a typical Brazilian tree with a high concentration of phenolic compounds, widely used for nutritional and medicinal purposes. In this perspective, the present research had as objective to carry out a technological prospection evaluating the world panorama of deposited patents. Questel - Orbit search and analysis software was used, including documents that had "pequi", "Caryocar brasiliense" or "pequizeiro" in the title, summary or claims. 128 patent documents have been identified. In 2002 there were the first deposits, since then every year there has been at least one deposit, until the moment the survey was carried out. The main depositary country was Brazil, the documents identified refer to different processes applied to obtain products for chemical conversion, with application mainly in the gastronomic and / or pharmaceutical area. Thus, the research points out an interest, mainly Brazilian, in the development of technologies attributed to this species.